Enterogenous cyst presenting as mediastinal mass in a newborn - Nidhi Jain; Vijay Gupta; N B Mathur; Ajay Kumar; Nita Khurana; Yogesh Kumar Sarin (Wolters Kluwer Medknow Publications, 2019)
Duplication cyst is a rare congenital malformation. Enterogenous cyst are foregut duplication cyst with or without a vertebral defect. We report a case of a 36hr old neonate with mediastinal enterogenous cyst associated with vertebral defects. The embryology, differentials, and management of enterogenous cyst in the newborn have been discussed.